Traditional beliefs prolong outbreaks of man-eating lions - Packer, Craig; Kushnir, Hadas; Ikanda, Dennis (Frontiers in Conservation Science, 2024)
From the 1800s to the 1950s, “spirit lions” and “spirit leopards” were blamed for countless deaths across Africa that were in fact caused by a combination of genuine carnivore attacks and murders instigated by witch doctors and secret societies. The widespread belief in supernatural spirit animals was viewed by the colonial authorities as rendering populations more vulnerable to further attacks by actual lions and leopards, as villagers were often reluctant to take concrete steps to eliminate the dangerous animals. Nearly a thousand people were attacked by lions in southern Tanzania between 1990 and 2006, involving 32 spatially discrete outbreaks that had been categorized by local communities as having been caused either by spirit lions or by real lions. Our interviews revealed that at least 40% of adults in three of the worst-hit districts believed in spirit lions and that this belief generally delayed their communities’ response. Consequently, outbreaks that were attributed to spirit lions persisted far longer than those attributed to real lions and included nearly twice as many victims. Belief in spirit lions declined with level of primary-school education, and male respondents were less likely to express a belief in spirit lions when interviewed by an American woman than by a Tanzanian man.